(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2022)
the article reflects on the viability of a socio-environmental restorative justice to deal with conflicts that affect nature and society, especially in countries in the global south, such as Brazil. In order to do so, the state of the art of the Brazilian restorative movement will be explained, presenting the characteristics of the institutionalization process of restorative practices carried out by the Judiciary, the types of conflicts covered and the restorative tools hegemonically adopted by judges (peacemaking circles). After that, will be questioned about the necessity to develop a new grammar of restorative justice, that should be applied to complex crimes, regarding the difficulty of victim affected by the act identification (and their legitimate forms of representation), the damage caused and, also, to establish a dialogue with the offenders when they are companies and corporations.